GERAKAN MASYARAKAT CERDAS MENGGUNAKAN OBAT (GeMA CerMat) PENCEGAHAN RESISTENSI ANTIBIOTIK PADA SISWA SISWI SMA DI KOTA KENDARI - Sabarudin, Sabarudin; Sahumena, Muhamad Handoyo; Mistryani, Mistryani; Rahman, Sudarman (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2019)
Antibiotic resistance to bacteria causes very dangerous consequences. Infectious diseases caused by bacteria that are not successful in treatment result in a prolonged illness. Some important aspects that must be considered regarding antibiotics include; Appropriate use, the selected antibiotic is the right antibiotic, only used for bacterial infections. The purpose of this service is intended to provide knowledge among students, especially high school students regarding the importance of preventing antibiotic resistance. The method used is the lecture method with the intention to provide direct understanding to the students of SMAN 10 Kendari and SMK Kesehatan on how to use antibiotics properly and correctly so that antibiotic resistance does not occur. Socialization begins with an explanation of the general definition of antibiotics, antibiotic classification, how to use antibiotics correctly and an explanation of the dangers of antibiotic resistance. Incorrect drug use often occurs in the community due to incomplete information delivered by health workers when giving drugs. The next socialization was an explanation of the procedure for storing and disposing of medicines that were good and right. Storage of drugs really needs to be considered to maintain the quality of medicinal products used, especially if the drug products run out in a long time. It is hoped that through this activity the objectives to be achieved can be realized and students and the community become more attentive in the use of antibiotics correctly.